Pelatihan Desain Modul Kimia Berbasis ESD dengan Pendekatan PjBL untuk Meningkatkan Kompetensi Guru MGMP Kimia - M, Munawwarah; Anwar, Muhammad; Herawati, Netti (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service program aimed to improve the competence of chemistry teachers in designing chemistry learning modules based on Education for Sustainable Development (ESD) through the Project-Based Learning (PjBL) approach. The program was conducted on April 25, 2026, in collaboration with the Chemistry Teacher Association (MGMP Kimia) of Pangkep Regency and involved 18 chemistry teachers. The implementation method consisted of preparation, material presentation, module development training, mentoring, product presentation, and evaluation. The evaluation was carried out through observation of the activity process, review of the module drafts, and questionnaires containing participants’ reflections and an analysis of students’ needs for the module from the teachers’ perspective. The results indicated that the participants were able to understand the basic concepts of ESD and PjBL, identify sustainability issues relevant to chemistry topics, and develop initial drafts of ESD-PjBL-based chemistry learning modules. The participants also demonstrated strong enthusiasm during the program, particularly in discussions, project idea development, and reflection on chemistry learning needs in schools. The needs analysis questionnaire showed that the need for module development was in the very high category, with an overall mean score of 3.62 and a score percentage of 90.42%. These findings indicate that ESD-PjBL-based chemistry learning modules are needed to support contextual, applicable, and sustainability-oriented learning. Therefore, this program contributed to strengthening teachers’ capacity to develop chemistry teaching materials that are relevant to students’ needs and the challenges of twenty-first-century learning